Making Transformative Geographies. Lessons from Stuttgart's Community Economy. - Schmid, Benedikt (transcript, 2020)
In the light of social and environmental unsustainability and injustice, the continuing attachment to the idea that a growth-based economy is reconcilable with human prosperity and ecological limits seems increasingly implausible. Tracing and dissecting the complexities of social change, thsi book speaks about the development of visions, alternatives, and strategies for a radical transformation beyond accumulation and growth. Covering an empirical sample of 24 eco-social organizations, projects, and groupings in the city of Stuttgart (Germany), the book drills down into the social, spatial, and strategic dimensions of transformation. It advances a conceptually and empirically grounded assessment of the possibilities and limitations of community activism and civic engagement for shifting transformative geographies towards a degrowth trajectory.
Keywords: Stadtgeografie; Stadtökonomie; Stadtforschung; Transformation; Sozioökonomischer Wandel; Sozialökologie; Projekt; Initiative; Kooperationsform; Gemeinschaftsarbeit; Wachstumsmodell; Wirtschaftswachstum; Kritik; Postwachstum; Sharing Economy